Magnetically induced enzymatic cascades-advancing towards multi-fuel direct/mediated bioelectrocatalysis - Herkendell, Katharina; Stemmer, Andreas; Tel-Vered, Ran (Nanoscale Advances, 2019)
A generic method to magnetically assemble enzymatic cascades on electrode surfaces is introduced. The versatile method enables the simultaneous activation of both direct and mediated electron transfer bioelectrocatalysis to harness different substrates, which can serve as multiple fuels and oxidizers in biofuel cells generating clean energy.
Created from Fastlane, Scopus look-up